Venezuela y Cuba. “Una seguridad diferente” - Carlos A. Romero (Centre de Recherches sur les Mondes Américains, 2009)
Venezuela has strengthened its ties with Cuba as part of an expanded vision of security.  "Cuba and Venezuela, two flags and one revolution," is an exclamation expressing the rapprochement between the two countries, their participation in the integration mechanism known as the ALBA and the development of political, military, economic and commercial exchanges. Fidel Castro sought to obtain subsidized prices for Venezuelan oil during his visit to Caracas in January 1959 and later he wanted to promote a similar revolutionary regime in Venezuela. Although he was unsuccesful in his support to the armed struggle, he later placed a role in the country through elections. The Cuban Revolution had not had an ally so close and so uncritical of its legacy in the region since the Sandinista Nicaragua. This paper discusses two dynamics in the relations between Venezuela and Cuba: the strategic alliance between the two countries since the year 1999 and their attempt at extending it in the region.